RECONSTRUCTING PROFESSIONAL COMMITMENT: EMOTIONAL EXHAUSTION AND RESILIENCE OF UNIVERSITY LECTURERS UNDER ACADEMIC STRAIN - Sofia Sofia; Abdullah Abdullah; Rahimah Embong (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
The professional commitment of lecturers in higher education is increasingly under pressure due to publication demands, administrative burdens, and continuous performance-based evaluations. This condition triggers emotional exhaustion, not only in physical exhaustion but also in the depletion of psychological energy and a reduction in the depth of work’s meaning. This research aims to understand the experience of emotional fatigue and the role of psychological well-being as a resilience mechanism in maintaining professional commitment. Using the qualitative Interpretative Phenomenological Analysis (IPA) approach, data were collected through in-depth interviews, observations, and documentation of lecturers from various universities. The results show that emotional exhaustion shifts professional involvement toward a more mechanistic, defensive stance. In contrast, psychological well-being, through self-acceptance, life goals, autonomy, personal growth, and positive relationships, can reconstruct the profession’s meaning and maintain commitment. This research contributes by presenting a resilience model based on psychological well-being in an academic context. So that means universities need to develop policies that not only reduce workload but also strengthen lecturers’ psychological foundations.